Mother of Dragons - Khalifa-Gueta, Sharon (Eikón / Imago, 2022)
Daenerys Targaryen’s metamorphosis scene is analyzed in this article, with accordance to the millennia old structure of the motif of “the woman and the dragon.” It is suggested in this article, that the visual manifestation of Daenerys in the HBO series Game of Thrones, is a reception of ancient Greco-Roma, and Early modern art. This article follows the iconography of four examples: the Minoan figurine of a priestess or goddess that holds serpents in her hands, Medea’s apotheosis on dragons-driven chariot from a vase painting, Saint Margaret wooden relic statue with the tiny dragon, and Cleopatra’s death by snakebites image. By following these examples an iconological line is drawn to connect between Daenerys visualization and the historic examples of the motif, demonstrating reception of not only visual issues but also concepts and meanings. Understanding iconographic and iconological reception in Daenerys television image reflect on conscious and unconscious aspects of her character and the way her figure engages with the viewers.